Assinatura elétrica de falhas paramétricas para diagnóstico de defeitos de soldagem de fios em encapsulamento MCP - Nascimento, Rafael Bez (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation describes a method of failure signature analysis by acquiring parametric data from 221 FBGA eMCP (embedded Multi Chip Package) encapsulation MMC devices. The objective is to identify the electrical signature of failure modes of the wire welding process through the failure signature represented in I-V curves. The application of the method identified failure modes such as open circuit, short circuit and differences in electrical circuit resistance associated with the inspected pins. The sample set analyzed was four hundred and forty-nine units of an eMCP package. The I-V curves, acquired from the samples with the developed tool and software, differed from the reference samples in 62 % of the cases. Among these samples, it was possible to identify similarities between the I-V curves in 84 % of the units. However, for samples where it was not possible to correlate I-V curves with known failure signatures, the results indicate which subsequent auxiliary methods of the failure analysis flow should be applied. Because data acquisition is done pin by pin. Therefore, this method applies to the location and isolation of the fault mechanism.
Keywords: Análise de falhas; Assinatura de falhas; Curva I-V; Soldagem de Fios; Failure Analysis; Fault Signature; I-V Curve; Wire Bonding; ACCNPQ::Engenharias::Engenharia Elétrica